TYPES AND REASONS OF CODE-SWITCHING IN TEACHING PROCESS OF THE ELEVENTH GRADE TEACHERS IN SENIOR HIGH SCHOOLS IN PALANGKA RAYA - Sitohang, Muston Nasib Martua; Usadiati, Wahyuningsih; Karani, Elanneri (Journal Compound: Improving the Quality of English Education, 2021)
The research was a descriptive qualitative research with the aim to analyze the types and reasons that caused the teachers in three schools with different accreditation to deliver the materials apply code-switching in English classes. The data were taken from the teachers of the eleventh-grade class from three schools based on A, B, and C accreditation, i.e. by interviewing the teachers and doing class observation. Result of the research showed that all of the three teachers applied code-switching in the class. The types of code-switching that they used were (a) inter-sentential code-switching, (b) intra-sentential code-switching, and (c) tag-switching. It was also found factors that caused the use code-switching in the English teaching process, they are (a) talking about a particular topic, (b) repetition used for clarifications, (c) softening or to strengthen request or command, and (d) because of real lexical needed. Types of accreditation did not show any difference in the teachers’ use of ode switching.